(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article deals with communicative and pragmatic features of the official style and the language means of information representation at the lexical, morphological and syntactic levels. Extralinguistic and linguistic factors, that determine the language systemic nature of this style, are described. Extralinguistic features of this functional type of language are emphasized in the paper. They are as follows official nature, the repetitiveness of actions and situations, thematic limitation, documentary. The main feature of the official style is its rational rather than emotional perception. The specific feature of the official style, which distinguishes it from other styles, is text standardization. The way of material representation with high and low standardization level is characterized. The vocabulary groups functioning (office terminology, synonyms, antonyms, paronyms) in the texts of documents is analyzed. The lexical level of official texts is represented by words that allow conveying the content of information accurately and unequivocally. The use of parts of speech forms (noun, adjective, verb forms, and prepositions) in documents is examined. The morphological peculiarity of these texts is that the official names of persons by profession, position, rank are masculine nouns. The facts of a verb forms transposition are analyzed. It is proved that the key feature of official texts is the affirmative word order which allows conveying the general meaning of the sentence without special pointing of its elements. A common syntactic phenomenon in the document is the splitting of predicates. Complex cases of syntactic government are examined. Communicatively relevant use of words and grammatical forms in the texts of documents makes it possible to represent official information accurately and logically according to the norms of the official style.